Effects of food-based approaches on vitamin A status of women and children: A Systematic Review - Nankumbi, J.; Grant, F.; Sibeko, L.; Mercado, E.; O’Neil, K.; Cordeiro, L.S. (Elsevier, 2023)
Abstract Background Vitamin A deficiency (VAD) increases risk for morbidity and mortality. Food-based approaches offer one strategy to improve vitamin A status.